The Power of Language in the Classical Period of Kalam - (:unkn) unknown (SCIENTIFIC STUDIES ASSOC-ILMI ETUDLER DERNEGI-ILEM, 2019)
When examining classical-era Warn books, we may be at first surprised by the great importance given to language in their theological discussions and the recognition of linguists (ahl al-lugha) as authorities. Whenever Muslim theologians (mutakallimun) deal with any issue, they first determine how the linguists would have made sense of the relevant terms and then explain it in a way that is appropriate for use in Arabic. This sensitivity to language is not only limited to defining the Islamic terms such as belief (iman), unbelief (kufr), disobedience (ma'siya), and justice (adl), but also includes defining the terms of physics and cosmology. In other words, when conceptualizing terms such as universe (a-alam), body (jism), substance (jawhar), accident ('arad), motion (haraka), and rest (sukun), these theologians mostly take into account how the speakers of language commonly use them. This article seeks to answer the question of why they regard language as an important discipline, alongside cosmological issues, in the context of the language-thought-existence relationship. Perhaps by making a thought system based on Arabic, which happened to emerge in their regions as a result of long-time interactions with the natural environment and consequently became conveyers of a particular worldview and way of thinking, they sought to resist the impact of the Greek worldview and logic that poured into the Islamic world from all lands via translations. In other words, the primary reason why the theologians considered language as the authority in theological and cosmological discussions was because they saw it, along with its structure and concepts, as a carrier of their traditional worldviews and way of thinking.
Keywords: Kalam; Language; logic; thought; existence; LINGUISTIC RELATIVITY